POTENCY OF MUNG BEAN SPROUT AS ENZYME SOURCE (α-AMILASE) - Suarni Suarni; Rauf Patong (Indonesian Journal of Chemistry, 2007)
Mung bean sprouts contain enzyme of α-amylase. A research on the effect of the sprout age and sprout varieties to the α-amylase activity and the protein level has been carried out in Laboratorium Bioproses BB Pascapanen Bogor using  Full Factorial Random Design with two factorials (1) sprout age; 1, 2, 3, 4, and 5 days as well as (2) varieties of mung bean; Kenari, Bhakti and Parkit.  Parameters observed were water and protein content of sprout, pH, activities of α-amylase, and dissolved protein in the enzyme extract. Results showed that the optimum temperature of α-amylase was 30 ºC, the highest protein level of sprout and the highest activity of α-amylase were given by the sprout of Bhakti at the age of three days. The water content in sprout was 65.23%, the protein level was 12.93 %, the dissolved protein in the enzyme extract was 2.88743 mg/mL, pH was 5.45, and the activity of enzyme was 4.09 Unit/mL. The potency of enzyme found in mung bean can be utilized in industries processing materials having high starch content, such as maize flour.